2004
DOI: 10.1111/j.1349-7006.2004.tb03254.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of DAP‐kinase is associated with poor survival in primary biliary tract carcinoma patients

Abstract: To clarify the clinicopathological significance of promoter hypermethylation of tumor suppressor and tumor-related genes in biliary tract carcinomas, we examined the promoter methylation status of multiple genes in primary biliary tract carcinomas. These consisted of carcinomas of the bile duct, gallbladder, and duodenal ampulla. Surgical specimens were obtained from a total of 37 patients with biliary tract carcinoma. The cohort consisted of 23 patients with bile duct carcinoma, 9 patients with gallbladder ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 45 publications
2
69
0
Order By: Relevance
“…The frequency in our study was comparatively higher than that in previous studies. Previous studies have revealed that the frequency of p16 promoter hypermethylation is not associated with tumor progression and clinicopathological characteristics [30,31] . Similarly, we found that p16 hypermethylation was not associated with any clinicopathological features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency in our study was comparatively higher than that in previous studies. Previous studies have revealed that the frequency of p16 promoter hypermethylation is not associated with tumor progression and clinicopathological characteristics [30,31] . Similarly, we found that p16 hypermethylation was not associated with any clinicopathological features.…”
Section: Discussionmentioning
confidence: 99%
“…P r o m o t e r hy p e r m e t hy l a t i o n o f p 1 6 l e a d s t o inactivation of the gene in various cancers. In gallbladder cancer, the frequency of p16 promoter hypermethylation ranges from 24% to 56% [12,[29][30][31] . In our study, p16 hypermethylation was found in 72.5% (37/51) of the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…RUNX3 was also identified as one of the five most informative genes of the CpG island methylator phenotype of colorectal cancer (Weisenberger et al, 2006). In addition to gastric and colon cancer, RUNX3 is frequently inactivated in cancers of the lung, bladder, pancreas, liver, prostate, bile duct, breast, larynx, esophagus, and testicular yolk sac by either DNA hypermethylation or mislocalization of the protein in the cytoplasm (Kato et al, 2003;Goel et al, 2004;Kang et al, 2004;Li et al, 2004;Tozawa et al, 2004;Xiao and Liu, 2004;Ito et al, 2005;Kim et al, 2005b;Lau et al, 2006). Among the lung cancers, RUNX3 promoter hypermethylation is preferentially found in lung adenocarcinomas (Sato et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…41 Additionally, loss of DAP-kinase expression in pituitary tumors, biliary tract tumors and urinary tract and gastric cancers and hepatocellular carcinoma was associated with advanced tumor stage and aggressive phenotype. 33,[42][43][44][45][46] A survey of breast tumors revealed that DAPk hypermethylation was observed mostly in the invasive subtype of tumors and was associated with poor prognosis. 31,47 In brain metastases of various solid tumors, DAPk silencing by methylation was observed in the majority of cases.…”
Section: Dapk Family and Cancer: A Novel Tumor Suppressor Family Of Pmentioning
confidence: 99%